1973
DOI: 10.1039/f19736900857
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen species adsorbed on CeO2/SiO2 supported catalysts

Abstract: The nature of the oxygen species adsorbed on slightly reduced Ce02/Si02 supported catalysts has been investigated using oxygen enriched with I7O2. The observed hyperfine splitting was found to be associated with the central component of the g tensor ; it indicated that the corresponding orbital contained the unpaired electron and therefore thecentral component was defined as gxx. With this assumption, the e.s.r. spectra are consistent with the adsorption of oxygen as 0; at 77 K with gyy = 2.0109,gxx = 2.0158 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 1 publication
4
27
0
Order By: Relevance
“…Therefore, the total spin density must be in the 2p orbital of the oxygen atom. Furthermore, taking only the A xx constant into consideration (since A yy ¼ 0 and A zz ¼ 0), the total spin density located between the two oxygen atoms of the O À 2 ion has been calculated when this latter was adsorbed on different matrices [85,86]. It has been found that the total spin density values are very close to unity when the a iso value is about 25 G. This value is similar to the one obtained in this study.…”
Section: Adsorption Of 17 O-enriched Molecular Oxygensupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, the total spin density must be in the 2p orbital of the oxygen atom. Furthermore, taking only the A xx constant into consideration (since A yy ¼ 0 and A zz ¼ 0), the total spin density located between the two oxygen atoms of the O À 2 ion has been calculated when this latter was adsorbed on different matrices [85,86]. It has been found that the total spin density values are very close to unity when the a iso value is about 25 G. This value is similar to the one obtained in this study.…”
Section: Adsorption Of 17 O-enriched Molecular Oxygensupporting
confidence: 82%
“…In some specific situations, the values for A zz have been determined [87] but rarely for A yy . Furthermore, the two oxygen nuclei are usually equivalent and this is due to adsorbed ionic molecular oxygen having its inter-nuclear axis (z direction) parallel to the surface [85,86]. Theoretical calculations lead to A xx values ranging between 74 G and 80 G, indicating that the localization of the unpaired electron on the O À 2 ion is largely independent of the support.…”
Section: Adsorption Of 17 O-enriched Molecular Oxygenmentioning
confidence: 95%
“…[4] Since the pioneering works of Yao and Yu Yao [2] and of Su et al, [5,6] many studies have been devoted to improving knowledge of the kinetics of OSC [7][8][9] and of the mechanisms implicated in surface and bulk oxygen mobility in ceria and related compounds, [10][11][12][13][14] with a special insight into CeZrO x oxides. [15][16][17][18][19] Oxygen diffusivity in these materials can be measured by 18 O/ 16 O isotopic exchange, [20][21][22] while oxygen species (e.g., superoxides, peroxides) that might be involved in the diffusion process can be investigated by electron spin resonance (ESR) [23][24][25][26][27] or FTIR. [18,[28][29][30][31] ESR studies have shown that the presence of a metal (Pt, Rh) drastically changes the nature of the oxygen species; the metal favoring the formation of O À ions instead of superoxide species.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen vacancies formed on the surface of the catalyst can be quantitatively investigated by means of EPR spectroscopy. 17,18,19,20 O 2 can be used as probe molecule for this purpose, because it binds to defects forming paramagnetic superoxide…”
Section: Epr Experiments Of O 2 Adsorptionmentioning
confidence: 99%